High Planting Density Combined with Delayed Topping Improves Short Fruiting Branch Cotton Yield by Enhancing Biomass Accumulation, Canopy Light Interception and Delaying Leaf Senescence - Yin Huang; Tao Wang; Xiaoxia Luo; Jianfei Wu; Yanfeng Deng; Qingquan Kong; Xiu Yang; Shuiping Xiao; Feiyu Tang (Agronomy)
Short fruiting branch cotton (SFBC) has a compact plant architecture suitable for dense planting. Plant population density (PPD) and topping are important agronomic practices to achieve high yielding by optimizing cotton plant structure. However, their individual and interactive effects on SFBC growth and yield are poorly understood. This study aimed to explore cotton growth and yield responses to various combinations of PPD and topping time (TT) and the underlying physio-ecological mechanism. Four combinations were included in a two-year field experiment (2023–2024) involving two PPD levels (5.3 plants m−2, low density LD; 8 plants m−2, high density HD) and two TT levels (early topping for leaving ten sympodials per plant ET; late topping for leaving fifteen sympodials per plant LT), and compared in terms of biomass accumulation, photosynthetically active radiation capture, and leaf senescence during entire reproductive growth period. Compared to the other three combinations, the combination of HD and LT (HDLT) achieved a higher lint yield due to a greater biological yield, which was predominantly attributed to the higher average rate during the rapid biomass increasing period. Owing to delayed leaf senescence caused by the HD and the LT, the HDLT performed better in leaf senescence-related attributes at the late growth stage. Moreover, these improved attributes also contributed to a higher radiation interception rate and photosynthetic efficiency at the late growth stage. Taken together, combining high density with later topping tends to increase the lint yield of SFBC through increasing dry matter accumulation, delaying leaf senescence, and enhancing canopy radiation interception rate at the late growth.